The Influence Of Motivation, Communication, And Work Discipline On The Performance Of Bank BTPN Employees - Retno Kurnia Adi Asri (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2023)
This study aims to determine the influence of motivation, communication, and work discipline variables on employee performance at PT. Bank BTPN, both particily and simultaneously. Data collection was carried out by distributing questionnaires, research conducted on 50 respondents, a sample of all Bank BTPN employees. Using Likert scale, respondents' answers were processed by multiple regression analysis, t test, F test and R2 test. Data collection techniques through the distribution of questionnaires using Likert scale. The data is then analyzed using statistical data processing. Based on the results of the analysis of hypothesis test data in this study shows that motivation (X1) has a significant effect on employee performance, communication (X2) has a significant effect on employee performance, work discipline (X3) has a significant effect on employee performance. Among the variables of motivation (X1), communication (X2), and work discipline (X3) that have the most dominant influence on the performance of Bank BTPN employees (Y) is the variable Work discipline (X3).